2013
DOI: 10.1007/s00436-013-3325-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Plasmodium falciparum infections in mild and severe malaria of children from Kampala, Uganda

Abstract: Diversity in parasite virulence is one of the factors that contribute to the clinical outcome of malaria infections. The association between the severity of Plasmodium falciparum malaria and the number of distinct parasite populations infecting the host (multiplicity of infection) or polymorphism within any of the specific antigen genes was investigated. The study included 164 children presenting with mild and severe malaria from central Uganda where malaria is meso-endemic. The polymorphic regions of the circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
75
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 42 publications
13
75
3
Order By: Relevance
“…The 79.69% prevalence of polyclonal infections found in the study population is consistent with results from other studies carried out in malaria endemic and high transmission intensity regions where multi-clonal infection rates varied from 50% to 100%, respectively [62][63][64][65][66][67] . The overall mean MOI of 3.39 in the study population found in our study corroborates with other studies in high malaria transmission areas in Africa like Kenya (2.83) 68 , Gambia (2.1), Senegal (2.2), Guinea Bissau (2.6), Guinea (4.0) 54 , Tanzania (3.5) 62 , Uganda (3.0-3.7) 65 and Madagascar (3.72-3.73) 66 but higher than results from low malaria transmission regions like Djibouti (1.0-1.4), Dakar (1.0-1.5), Niamey (1.0-1.8) 67 and Sudan 69 . The high MOI found in this study maybe due to the boosted parasite specific immunity in people residing in high malaria transmission regions and the study population as children were reported to carry higher MOI infections compared to adults 38,70 .…”
Section: Discussionsupporting
confidence: 90%
“…The 79.69% prevalence of polyclonal infections found in the study population is consistent with results from other studies carried out in malaria endemic and high transmission intensity regions where multi-clonal infection rates varied from 50% to 100%, respectively [62][63][64][65][66][67] . The overall mean MOI of 3.39 in the study population found in our study corroborates with other studies in high malaria transmission areas in Africa like Kenya (2.83) 68 , Gambia (2.1), Senegal (2.2), Guinea Bissau (2.6), Guinea (4.0) 54 , Tanzania (3.5) 62 , Uganda (3.0-3.7) 65 and Madagascar (3.72-3.73) 66 but higher than results from low malaria transmission regions like Djibouti (1.0-1.4), Dakar (1.0-1.5), Niamey (1.0-1.8) 67 and Sudan 69 . The high MOI found in this study maybe due to the boosted parasite specific immunity in people residing in high malaria transmission regions and the study population as children were reported to carry higher MOI infections compared to adults 38,70 .…”
Section: Discussionsupporting
confidence: 90%
“…[7][8][9][10][11][12][13][14][15][16][17] Since treatment with drugs of malaria patients is an integral part of malaria control and prevention strategy and the selected markers can be used as drug efficacy markers, knowing the baseline population structure of circulating parasites in an endemic country will aid in monitoring change in transmission pattern as well as efficacy of drugs that are in use. In this study, pretreatment patients were enrolled and genotyped to know parasite population structure and provide a baseline data for future reference.…”
Section: Discussionmentioning
confidence: 99%
“…5 Genetic diversity of the parasite arises during adjustment with different environmental and immunological factors such as drugs, host immune systems, and transmission intensity, and it contributes to the parasite's virulence. 6,7 Several P. falciparum genes have been found to show extensive genetic polymorphism. This phenomenon has been exploited for assessing the genetic diversity and population dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations